2007
DOI: 10.1080/00016340701415236
|View full text |Cite
|
Sign up to set email alerts
|

Serum markers of macrophage activation in pre‐eclampsia: no predictive value of soluble CD163 and neopterin

Abstract: The macrophage serum-markers sCD163 and neopterin are not pre-symptomatic nor prognostic markers for pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
1
17
0
1
Order By: Relevance
“…Seven of these studies were conducted in the United States [8,19,[21][22][23][24][25]; eleven, in Europe [9,[26][27][28][29][30][31][32][33][34][35]; and one, in Australia [36]. Only four studies were conducted in low and middle-income countries [12,17,37,38] (Table 1).…”
Section: Description Of Systematic Literature Review Studiesmentioning
confidence: 96%
See 3 more Smart Citations
“…Seven of these studies were conducted in the United States [8,19,[21][22][23][24][25]; eleven, in Europe [9,[26][27][28][29][30][31][32][33][34][35]; and one, in Australia [36]. Only four studies were conducted in low and middle-income countries [12,17,37,38] (Table 1).…”
Section: Description Of Systematic Literature Review Studiesmentioning
confidence: 96%
“…Five out of 23 studies used plasma specimens to evaluate the CRP levels [9,29,32,33,37], and two studies did not specify the specimen type [12,36]. All other studies reported the use of serum in the CRP assay [8,17,19,[21][22][23][24][25][26][27][28]30,31,34,35,38] (Table 1).…”
Section: C-reactive Protein and Preeclampsiamentioning
confidence: 97%
See 2 more Smart Citations
“…Another researchers pointed out decreased CD163 expression on monocyte surface of preeclamptic pregnants compared with normotensive pregnants [41]. Kronborg et al observed no difference between preeclamptic and normotensine pregnants for parameter of soluble macrophage serum marker sCD163 [42]. Schonkeren et al reported significantly increased CD163 expression in preterm preeclamptic decidua basalis compared with preterm control pregnancies [43].…”
Section: Discussionmentioning
confidence: 98%